The Portrayal of Orientalism and Occidentalism in the novel "A Passage to India" by, E. M. Forster Post-Colonialism Approach - Delis Aprianti (Channing : Journal of English Language Education and Literature, 2022)
This research was conducted to analyze the influence of orientalism and occidentalism on the lives of western and eastern people in the novel "a passage to india" by e. M. Forster using a post-colonial approach and the theory of edward said, namely Orientalism and Occidentalism. According to Said, Orientalism is the study of Eastern world in the perspective or Western people and Occidentalism is the study of Western world in the perspective of Eastern people. This study used qualitative methods to analyze the potrayal and influence of the two theories in their respective social lives. Based on the analysis that has been done in the novel “A Passage to India”, Western people in India still monopolize the government and look down on Indian. Although there are some characters who have welcomed and treated Indians well but their initial interest in coming to India was to rule India.